IMPLEMENTATION OF LOCAL AREA NETWORK SECURITY USING THE SITE ACCESS BLOCKING METHOD ON LAYER 7 PROTOCOL MIKROTIK RB 941-2ND - Arina Selawati; Rizka Dahlia (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Computer networks are a highly sought-after service today. A computer network is a connection that allows two or more devices to physically or logically communicate with each other to exchange data and information. Managing a local area network (LAN) is one alternative solution to this problem to achieve optimal service. A key consideration in managing a local area network is network security, which involves regulating and restricting user access to websites. This aims to improve security and prevent network access from heavy traffic, caused by unproductive website access during work hours, excessive bandwidth usage, and the threat of cyberattacks. One network device that has features for implementing or activating computer network security is the MikroTik router. MikroTik firewalls contain Layer 7 Protocols, which contain parameters such as protocol, destination port, source port, and content. If traffic separation is not possible, we can consider using the Layer 7 Protocol or L7-protocol feature.